The Effect of Self-Efficacy, Management Capability, and Internal Communication Onteachers’ Organizational Commitment - Osberth Sinaga; Munajat Munajat; M. Joharis Lubis (BIRCU, 2020)
This study aims to investigate the effect of Self-Efficacy, Management Ability, and Internal Communication on Teachers’ Organizational Commitment at Dwi Warna Senior High School Medan. The amount of population is 52 people and the sample is 30 people. The distribution data shows that 62.30% is included in the Fair category and 37.70 in the less category. The data distribution of Self-efficacy categorizes that 65.90% is included in the fair category and 34.10% in the less category. The distribution of Management Capability data shows that 64.40% is included in the high category and 35.60% in the fair category. The distribution of Internal Communication data shows that 68.20% is included in the high category and 31.80% in the fair category. The results obtained from the calculation are 50.394. The F table is calculated with the provisions of the significance level of 95% and alpha 5% and degrees of freedom with provisions n - 1 = 29. With these provisions obtained lift Ftable = 2, 85 Thus the value of Fcount = 50.394, and Ftable = 2.85. Because Fcount > Ftable which means that Ho is rejected and Ha is accepted, so it can be concluded that there is a significant simultaneous influence between self-efficacy, Management Capability, Internal Communication on Organizational Commitment.